ANALYSIS OF BLOOD FLOW THROUGH STENT IN COMMON CAROTID ARTERY - Satriawan, Muhammad Bagas Yudanto; Winarto, Winarto; Yuliati, Lilis (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2026)
The human body's circulatory system consists of many blood vessels, one of which is the carotid artery. However, the carotid artery in blood circulation is prone to carotid stenosis. A common method to cure carotid stenosis is to install a stent in the vessel. One of the most important parameters of stenting to prevent stenosis is the blood flow shear stress on the stent wall. After installing a stent, there is still a possibility of blockage again in the blood vessel, which is called in-stent restenosis. The number of stent cells is one of the main parameters that affect the blood flow and shear stress as well. In this research, the number of cells was varied to examine their effect on time-averaged wall shear stress, oscillatory shear index, and stent structural deformation with the computational fluid dynamics method by considering fluid-structure interaction. The result showed that the greater the number of cells, the higher the time-averaged wall shear stress and the lower the oscillatory shear index. This means a higher number of cells results in a smaller possibility of stenosis. Moreover, a stent with six cells has higher deformation than the other stents. This research provides a reference to estimate the possibility of carotid artery stenosis disease.